Position of Dispute Resolution Institutions in the Financial Services Sector: Analysis of Regulation No. 1/POJK.07/2014 in Disputes Over Islamic Gold Payments - Rizal Ramadhani (IHSA Institute, 2022)
The role of Islamic banks in the economy is still relatively small due to several obstacles, namely not yet optimal consumer protection and disruption of the financial system. The development of Sharia-based products is increasingly widespread in Indonesia, and Pegadaian is no exception. The purpose of this research is to identify and study contracts in Islamic banking business activities related to gold pawn services at BRI Syariah banks, to know and understand the position of alternative dispute resolution institutions in the financial services sector in sharia gold pawning product disputes. This research is descriptive analytical research, namely research that conveys an overview of the existing facts supported by applicable and applied provisions. The method used is the Normative Juridical Approach Method, namely the Legal Research Method of Library/Secondary Data. In this study using the Qualitative Method, so that the existing data is then analyzed qualitatively based on the existing laws and regulations as a positive legal norm so that it does not use statistics or formulas. Contracts and Legal Aspects in Islamic Banks, the contracts carried out have worldly and hereafter consequences because the contracts are based on Islamic law. Often customers dare to violate the agreement/agreement that has been made if the law is only based on positive law, but this is not the case if the agreement has accountability until yaumil qiyamah later. Every contract in Sharia Banking, both in terms of goods, transaction actors, and other provisions, must meet the provisions of the contract. What must be noted is that consumers cannot immediately resolve disputes through LAPS. Article 2 of POJK Number 1/POJK.07/2014 concerning Alternative Dispute Resolution Institutions in the Financial Services Sector regulates procedures for resolving complaints. Where, the complaint settlement mechanism must first be resolved directly with the PUJK. This step is called the Internal Dispute Resolution (IDR). Islamic banking needs to prepare Human Resources who are not only equipped with Islamic Economics skills, but also have a legal background because Islamic Banking Operational Activities are not only based on Islamic Sharia, but are also bound by statutory provisions in the Indonesian National Legal System.